Complete traumatic transection of urethra and vagina in a child - Bao T. Truong; Mark A. Rich; Hubert S. Swana (Elsevier, 2016)
Urethral injury in females is rare in the absence of pelvic fracture. We report a case of a five year-old girl who sustained sharp perineal trauma that resulted in complete transection of both the vagina and urethra. We discuss management and review the literature.